2004
DOI: 10.1152/ajpheart.00958.2003
|View full text |Cite
|
Sign up to set email alerts
|

Preserved flow-mediated dilation in the inactive legs of spinal cord-injured individuals

Abstract: .-The aim of the study was to assess endothelial function, measured by flow-mediated dilation (FMD), in an inactive extremity (leg) and chronically active extremity (arm) within one subject. Eleven male spinal cord-injured (SCI) individuals and eleven male controls (C) were included. Echo Doppler measurements were performed to measure FMD responses after 10 and 5 min of arterial occlusion of the leg (superficial femoral artery, SFA) and the arm (brachial artery, BA), respectively. A nitroglycerine spray was ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
116
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(140 citation statements)
references
References 52 publications
19
116
5
Order By: Relevance
“…79,80 In the only study to investigate resistance artery remodeling in SCI, individuals with chronic SCI exhibited a 40-60% reduction in SFA-reactive hyperemia compared with AB individuals. 67 This far exceeds values that occur in healthy AB individuals who undergo acute 81 or chronic 82 bed rest. Remodeling of resistance arteries appears to be at least partly attributable to general muscle atrophy, as lower-limb-reactive hyperemia corrected per unit muscle volume is similar between SCI and AB.…”
Section: Resistance Arteries Structural Adaptationsmentioning
confidence: 90%
See 2 more Smart Citations
“…79,80 In the only study to investigate resistance artery remodeling in SCI, individuals with chronic SCI exhibited a 40-60% reduction in SFA-reactive hyperemia compared with AB individuals. 67 This far exceeds values that occur in healthy AB individuals who undergo acute 81 or chronic 82 bed rest. Remodeling of resistance arteries appears to be at least partly attributable to general muscle atrophy, as lower-limb-reactive hyperemia corrected per unit muscle volume is similar between SCI and AB.…”
Section: Resistance Arteries Structural Adaptationsmentioning
confidence: 90%
“…61 In the only study to investigate brachial artery FMD, it was reported that absolute brachial artery FMD is not different between SCI and AB individuals, whereas brachial artery FMD expressed relative to the shear rate stimulus (in this case the change in shear rate ratio from rest to peak hyperemic response) was reduced in SCI compared with AB. 67 Enhanced or preserved FMD below the lesion and a reduction in FMD above the lesion appears counterintuitive given the known positive relationship between the degree of physical activity and FMD in AB. [70][71][72] Such differences in FMD above and below the lesion may be attributed to the structural adaptations that occur following SCI.…”
Section: Conduit Arterial Function After Sci Structural Adaptationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus it is somewhat counterintuitive to have research show that with deconditioning flowmediated dilatation (FMD), a method of noninvasively assessing endothelial health, is actually increased in the legs of individuals with SCI and decreases to normal levels with training. 14,18 It has been suggested that this results from increased shear stress, a strong stimulator of NO release, in the leg vasculature of individuals with SCI, 18 which may increase endothelial nitric oxide synthase (eNOS). With larger arterial diameters following FES-LCE training, 19 shear stress is reduced which may decrease eNOS and FMD while concurrently increasing arterial compliance.…”
Section: Effects Of Fes-lce Training On Arterial Compliance D Zbogarmentioning
confidence: 99%
“…[3][4][5] In humans with longstanding SCI, extensive adaptations occur in the peripheral circulation such as a 30% decrease in diameter, a reduction in blood flow, and an almost doubling of stress levels in the femoral artery. 1,[6][7][8] Results on vascular changes derived from other models of deconditioning like bedrest studies [9][10][11] conflict with some studies showing a decrease in leg blood flow and others showing no changes after a period of bedrest varying from 10 to 41 days. However, none of these studies provides information related to changes in diameter size, and the magnitude of physical inactivity during bedrest may vary, because movements of the legs are still possible.…”
mentioning
confidence: 99%